Comparison, Fusion, and Bricolage: How to Integrate Islamic Philosophy within Comparative Philosophy - Albertini, Tamara (Journal of Chinese philosophy, 2024)
The launching of philosophical pursuits undertaken in an East-West trajectory at the first East-West Philosophers’ Conference in 1939 represents a turning point in philosophy. However, as groundbreaking as this approach was, it left out all philosophical cultures that did not fit the initial framework. Islamic philosophy, being viewed as neither Western nor Eastern (Asian), was thus marginalized from the start. I introduce “Bricolage” – a method emphasizing curiosity, humility, and playfulness – as a more nuanced way of engaging with diverse philosophical traditions. “Bricoleurs” are interculturalists who remain open to the use of different methodologies: they are “flâneurs” walking through diverse philosophical landscapes for sheer intellectual pleasure.